2006
DOI: 10.1099/vir.0.81579-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of two severe acute respiratory syndrome (SARS) vaccine candidates in mice challenged with SARS coronavirus

Abstract: Two different severe acute respiratory syndrome (SARS) vaccine strategies were evaluated for their ability to protect against live SARS coronavirus (CoV) challenge in a murine model of infection. A whole killed (inactivated by b-propiolactone) SARS-CoV vaccine and a combination of two adenovirus-based vectors, one expressing the nucleocapsid (N) and the other expressing the spike (S) protein (collectively designated Ad S/N), were evaluated for the induction of serum neutralizing antibodies and cellular immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
164
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(178 citation statements)
references
References 54 publications
5
164
1
1
Order By: Relevance
“…Our preliminary studies showed clinical signs, viral replication and lung pathology in ferrets infected with SARS-CoV reflecting pathogenesis in humans ; we therefore decided to evaluate and compare our two SARS vaccine candidates (WKV and Ad expressing S and N protein) in a single trial in the ferret model (Kobinger et al, 2007). This is the first report of two SARS vaccine formats tested directly against each other in both mice (See et al, 2006) and ferrets. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our preliminary studies showed clinical signs, viral replication and lung pathology in ferrets infected with SARS-CoV reflecting pathogenesis in humans ; we therefore decided to evaluate and compare our two SARS vaccine candidates (WKV and Ad expressing S and N protein) in a single trial in the ferret model (Kobinger et al, 2007). This is the first report of two SARS vaccine formats tested directly against each other in both mice (See et al, 2006) and ferrets. …”
mentioning
confidence: 99%
“…N protein has been shown to generate CoV-specific CD8 + T cells (Boots et al, 1991;Seo et al, 1997; Stohlman et al, 1993 Stohlman et al, , 1995; it also provides protection in animals in response to infection by animal CoV (Collisson et al, 2000;Seo et al, 1997). In addition, vaccination with SARS N protein decreased replication of a vaccinia virus expressing SARS N protein in mice (Kim et al, 2004).The SARS Accelerated Vaccine Initiative (SAVI) (Finlay et al, 2004) described the first head-to-head comparison of a WKV SARS-CoV vaccine and a combination of attenuated Ad expressing either S or N glycoproteins (Ad S/N) for their ability to protect against live SARS-CoV challenge in a mouse model (See et al, 2006). In the mouse model, the WKV vaccine, in the presence or absence of alum adjuvant, provided protection against live SARS-CoV challenge by the induction of high levels of neutralizing antibodies and reduced SARS-CoV load in the respiratory tract compared with mock-vaccinated mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies demonstrated that a sub lingual immunization can prevent the viral vector entry into the brain (Shim et al, 2012). Also, an intranasal route of vaccination was shown to protect mice from SARS-CoV challenge better than an intramuscular delivery of the same vaccine (See et al, 2006;Hu et al, 2007). Expression of full length S protein is shown to result in enhanced hepatitis or infection whereas, expression of just the ectodomain of S protein eliminated infection enhancement (Weingartl et al, 2004;Yang et al, 2005b).…”
Section: Vaccines and Immunotherapy For Sars-covmentioning
confidence: 99%
“…(Lin et al, 2007). Hypersensitive appropriate animal model (See et al, 2008) reaction upon post-immunization viral challenge in mice (Kam et al, 2007;Tseng et al, 2012) Recombinant vector Disease exacerbation upon SARS-CoV Protective in mice, ferrets, monkeys, Vaccines (Adenovirus, challenge in some cases (Czub et al, 2005) hamsters (Bukreyev et al, 2004; Poxvirus or recombinant) See et al, 2006;Napoli et al, 2007;See et al, 2008) …”
Section: Vaccines and Immunotherapy For Sars-covmentioning
confidence: 99%